Numerical study of initial gas temperature impact on plasma characteristics of argon switch discharge - Zheng, Shichao; Sun, Rongrong; Liu, Hanlin; Ma, Linlin (AIP advances, 2025)
In this paper, a two-dimensional fluid model based on plasma chemistry was employed to numerically simulate the streamer discharge process in an argon spark switch. The two electrodes of the argon switch adopted a rod–rod structure with hemispherical heads. The distributions of plasma parameters, including particle density, current, and electric field strength at various times, were acquired and subjected to analysis. In addition, the effect of different initial gas temperatures (300–400 K) on plasma characteristic parameters, such as the breakdown time delay of the streamer discharge and the electric field strength of streamer head, was investigated. Linear fitting functions for breakdown time delay and average electric field strength under different initial gas temperatures were proposed separately. This research can provide theoretical guidance on the influence of different initial gas temperatures on plasma characteristic parameters in the streamer discharge process of a gas switch.